Estimated of two freshwater snails ability on bioaccumulation of some elements in soft tissue and shell - قاسم محمد ابو تراب, مفيد; هادي محسن القاروني, عماد; طالب السعد, حامد (University of Thi-Qar Journal of Science, 2017)
The ability of snails Melanopsis nodosa and Lymnaea auricularia has been estimated on bioaccumulation for Zn,Al, Li, V, Ce and P in soft tissue and shell. Significant correlation for Zn, Al and P concentration was found in bothspecies. The amount and ability of bioaccumulation for all elements in the two species were convergent except for Al it was in L. auricularia higher than M. nodosa more than four times. The concentrations of Zn, Al, V, Ce in soft tissue were higher than shell in both species except Li it was high in L. auricularia shell in comparison with the soft tissue.The elements followed this order P < Al< Zn< V< Li <Ce in soft tissue and shell except for L. auricularia shell inwhich Al concentration is more than P.